Vitamin K epoxide reductase complex 1 (VKORC1) haplotypes in healthy Hungarian and Roma population samples. (June 2009) - Sipeky, Csilla; Csongei, Veronika; Jaromi, Luca; Safrany, Eniko; Polgar, Noemi; Lakner, Lilla; Szabo, Melinda; Takacs, Istvan; Melegh, Bela
The aim of this work was to determine the VKORC1 haplotype profile in healthy Hungarian and Roma population samples, and to compare our data with other selected populations. Using haplotype tagging SNPs (G-1639A, G9041A and C6009T), we characterized Hungarian (n = 510) and Roma (n = 451) population samples with regard to VKORC1*1, *2, *3 and *4 haplotypes. In the Hungarian samples, the VKORC1*1, *2, *3 and *4 haplotypes accounted for 3, 39, 37 and 21%, respectively and by contrast, in the Roma population samples the VKORC1 variants were 5, 30, 46 and 19%, respectively. Comparing the genotypes of Roma and Hungarian populations, difference was found in the *2/*2 (6.87 vs 13.5%), *2/*4 (13.9 vs 19.2%) and *3*3 (21.9 vs 13.7%) VKORC1 haplotype combinations. Comparing each group with the others, and our data with findings published previously by other groups, the VKORC1 genetic profile in Hungarians was more similar to European Caucasians and Americans with European descent than to Roma samples. Clear differences could be detected between Roma versus Hungarians and European or American Caucasians; the Roma population had only minor similarities with data from India.